Monitoring dan Evaluasi Pelaksanaan Strategi Directly Observed Treatment Shortcourse sebagai Upaya Penanggulangan Tuberculosis di Puskesmas yang Berada dalam Lingkup Pembinaan Dinas Kesehatan Kabupaten Subang - Felix Kasim; Mary Soen; Katrin Fitria Hendranata (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Background: The implementation of the DOTS strategy in health centers aims to, among others, reduce morbidity rates and break the chain of transmission. Indonesia ranks third on the incidence of TB cases. In general, this research aimed to investigate the effort implementation, barriers, benefits and expectations in implementing the DOTS program in 40 health centers within the work area of Subang District Health Office. Methods: This was a qualitative study. Data collection technique was in-depth interviews to the head of health centers and P2TB officers, the DOTS corner participation observation and Focus Group Discussion of TB officers. The research instruments were recorder and camera. The number of population was 40 health centers taken with cluster random sampling technique and the number of samples was 10 health centers, represented by 10 heads of the health centers and 10 P2TB officers. Results: This study found out things such as efforts, barriers, benefits and expectations of the implementation of the DOTS strategy in the health centers of Subang District. The efforts made in 10 health centers were good enough, with some constraints such as lack of laboratory infrastructure, lack of human resources, intersectional collaboration, medication compliance, and the role of PMO personnel, economic factors and poor public education, drug distribution delays, difficulties in recording and reporting of patient transfer. Therefore, improvements should be done in cross-sectoral communication, completeness of lab infrastructure, empowerment of each village cadre for education and networking. Conclusion: In 10 health centers (Pagaden, Gunung sembung, Kalijati, Binong, Purwadadi, Palasari, Cisalak, Kasomalang, Sagalaherang, and Serang Panjang) DOTS program had been done in an effort to overcome tuberculosis in accordance with the 5 elements of DOTS. Latar belakang: Pelaksanaan strategi DOTS di puskesmas salah satunya bertujuan mengurangi angka kesakitan dan memutus rantai penularan. Indonesia menduduki peringkat ketiga insidensi kasus TB. Secara umum penelitian ini bertujuan adalah untuk mengetahui upaya pelaksanaan, kendala-kendala, manfaat dan harapan dalam menjalankan program DOTS di 40 Puskesmas yang berada dalam lingkup pembinaan Dinas Kesehatan Kabupaten Subang. Metode: menggunakan metode kualitatif, teknik pengumpulan data wawancara mendalam Kepala Puskesmas dan Petugas P2TB Puskesmas, Observasi Partisipasi Pojok DOTS, serta Focus Group Discussion kader TB, instrumen penelitian berupa alat perekam dan kamera, jumlah populasi 40 Puskesmas, teknik pengambilan sampel Cluster Random Sampling, jumlah sampel 10 Puskesmas, diwakili 10 kepala Puskesmas, 10 petugas P2TB. Hasil: penelitian, didapatkan upaya, kendala, manfaat dan harapan pelaksanaan Strategi DOTS di Puskesmas Kabupaten Subang. Kesimpulan: upaya yang dilakukan di 10 Puskesmas sudah cukup, dengan beberapa kendala seperti ketiadaan sarana prasarana laboratorium, kurangnya SDM, kerja sama lintas sektoral, kepatuhan minum obat, peran dan tenaga PMO, faktor ekonomi dan rendahnya pendidikan masyarakat, keterlambatan pendistribusian obat, sulitnya pencatatan dan pelaporan pasien pindah dan pindahan. Sebaiknya dilakukan komunikasi lintas sektoral, mengusahakan kelengkapan sarana-prasarana lab, pemberdayaan kader tiap desa untuk penyuluhan dan penjaringan.